(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
Drawing on the traditions of existential-phenomenology and depth psychology, this article explores the origins of technology in the 15th-century invention of linear perspective vision, and proposes that its continuing unconscious presence in contemporary life is as a tension of alienation and homecoming